2010
DOI: 10.1080/03630242.2010.498752
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs About Breast Cancer and Help-Seeking Intentions for the Disease Among Women in India

Abstract: Breast cancer is the most frequently occurring malignancy among women in India, however, the recorded stage distribution at presentation in India is less favorable than in Europe. Health beliefs are important in help-seeking for potential symptoms of disease, which may be particularly important among women who do not have access to breast screening programs. The purpose of this study was to examine Indian women's beliefs about breast cancer and help-seeking for the disease and how these beliefs related to thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…The PBC measures correlated significantly (r = −.246, p < .001). Cronbach's alpha for the product items is rather low (α = .68), which is not surprising as it is already reported in several studies that PBC scales tend to have a low internal reliability (Askelson et al, 2010;Grunfeld, & Kohli, 2010;Klöckner & Matthies, 2009;Roncancio, Ward, & Fernandez, 2013). "Self-efficacy" was also rated on a six-point Likert-type scale with each respondent indicating their confidence to overcome each barrier (1 = not at all confident to 6 = very confident).…”
Section: Pbc and Self-efficacymentioning
confidence: 55%
“…The PBC measures correlated significantly (r = −.246, p < .001). Cronbach's alpha for the product items is rather low (α = .68), which is not surprising as it is already reported in several studies that PBC scales tend to have a low internal reliability (Askelson et al, 2010;Grunfeld, & Kohli, 2010;Klöckner & Matthies, 2009;Roncancio, Ward, & Fernandez, 2013). "Self-efficacy" was also rated on a six-point Likert-type scale with each respondent indicating their confidence to overcome each barrier (1 = not at all confident to 6 = very confident).…”
Section: Pbc and Self-efficacymentioning
confidence: 55%
“…This is a serious concern due to the implications of rising cancer rates (Takiar et al, 2011) as well as more far-reaching consequences, such as national healthcare costs. Our search revealed one study that assessed four of Leventhal's illness representations (identity, timeline, consequences, cure/control) among 800 women in Allahabad, India (Grunfeld and Kohli, 2010). Respondents indicated relatively neutral beliefs about the timeframe and consequences associated with cancer and slightly positive beliefs about controllability of breast cancer.…”
Section: 845 Illness Representations Of Cancer Among Healthy Residenmentioning
confidence: 99%
“…In particular, health communication campaigns should highlight the benefits of obtaining a mammogram, even when there is no history of breast cancer in the family. Existing research (e.g., Grunfeld & Kohli, 2010) has indicated that rural Indian women believe that they would be discouraged from seeking help for breast cancer. It is noteworthy that this study underscores the importance of messages promoting mammography to be framed such that they highlight the benefits toward the whole family, as well as form a part of at-risk asymptotic women's routine health care regimen.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, Grunfeld and Kohli (2010) examined Indian women's beliefs about breast cancer and help-seeking to understand how these influenced their intentions to seek help for breast cancer symptoms. Grunfeld and Kohli found that the respondents held negative beliefs about breast cancer, suggesting that messages providing beneficial information about the contribution of mammograms in the overall health Communication Research Reports 237 care routine of at-risk women should influence intentions toward obtaining mammograms.…”
Section: Breast Cancer Screening Beliefs In Indian Womenmentioning
confidence: 99%
See 1 more Smart Citation